Viroid infection and rootstocks affect productivity and fruit quality of the Tunisian citrus cultivar Maltaise demi sanguine - Najar, Asma; Hamrouni, Lamia; Bouhlel, Rym; Jemali, Ahmed; Jamoussi, Bassem; Durán-Vila, Núria (2018)
In Tunisia, sweet orange citrus cultivars are usually grafted on sour orange rootstock. However, this rootstock is susceptible to Citrus tristeza virus (CTV). A trial was established in 2005 to evaluate the performance of newly introduced rootstocks compared to sour orange, using the sweet orange cultivar 'Maltaise demi sanguine' as the grafted scion. The effect of single or mixed viroid infections were monitored over 12 years. Once established, tree growth, cumulative yield, tree performance and fruit quality of 'Maltaise sweet orange' were assessed from 2008. Mixed viroid infections caused significant decreases (39 to 60%) in the canopy volume of 'Maltaise' grafted on Carrizo citrange, Swingle citrumelo, Cleopatra mandarin, Rangpur lime, Volkamer lemon and Trifoliate orange. The cumulative yield of trees grafted on'Alemow' (Citrus macrophylla) and inoculated with Hop stunt viroid (HSVd) was 76% less than the healthy control. Mixed infections caused production decreases of 56% from trees grafted on Swingle citrumelo and 69% from those grafeted on Trifoliate orange. When quality parameters of fruit from trees infected with each viroid, and combinations of viroids were compared, no significant differences were recorded.